SURVEY KEPUASAN KONSUMEN PADA KUALITAS LAYANAN FRONT OFFICE STAFF PT. MANDALA MULTIFINANCE, Tbk.CABANG MAKASSAR RAYA - Lukman Lukman; Diva Amirah Nuzaibah, Fadhilah Nurkhalishah, Fadillah Putri Arisa, Fatima Az’zahra A. Muh. Ilyas Sam (Adiba Aisha Amira, 2022)
PT. Mandala Multifinance, Tbk. business-focused commercial finance company motorcycle financing, electronics, furniture, and other multipurpose financing. Image of a company is also influenced by consumer satisfaction itself. Consumer satisfaction can increase the intensity of purchases by consumers, thereby creating a level of satisfaction high consumers, it can create consumer loyalty. Consumer satisfaction survey carried out with the aim of evaluating the extent to which the level of customer satisfaction with the services provided by operational staff. The population in this study are consumers of PT. Mandala Multifinance, Tbk at the Makassar Raya branch (Makassar, Makassar 3, and Gowa) which received service from the front office staff. Sampling using non-probability sampling with accidental sampling technique. The number of samples in this study were 90 respondents. Research result which were analyzed using the Community Satisfaction Index (IKM) compiled by the Service Unit Government shows the results of the quality of service unit performance is very good. Insufficient company services to consumers, namely the response or speed in staff service,staff availability in serving, and initiatives in helping consumers. As for the advantages namely the comfort of the waiting room, the cleanliness of the waiting room and friendliness, courtesy, and attitude in service.